(untitled) (Zaporizhzhia Historical Review, 2021)
Panas Peter Lyubchenko (1897–1937) is one of the most enigmatic and the most influential representatives of party-soviet elite in 20-30 years of the last century. Thus the detailed modern research of political and personal biography of this figure is absent until now. The work of P.P.Bachinskiy «Panas Peter Lyubchenko: one of most prominent party figures of Ukraine (1897–1937)», that was published has a lot of «white spots»and was prepared on the basis of marxismleninism. At the end of the 80th - the beginning of the 90th the row of works were published the authors tried and their research exactly «white spots» in the political and vital Panas Peter Lyubchenko”s biography were published, but also they did not answer all questions. Unknown until now there is his personal position in relation to the leadthrough of the collectivization, hunger of 1932-1933, political repressions of 30s years of the last century.